Protective property of mulberry digest against oxidative stress – A potential approach to ameliorate dietary acrylamide-induced cytotoxicity. (1st September 2017) - Zhang, Linxia; Xu, Yang; Li, Yuting; Bao, Tao; Gowd, Vemana; Chen, Wei
Abstract: The aim of this study was investigating the protective effect of mulberry digest (MBD) on acrylamide-induced oxidative stress. Composition analysis of MBD revealed that it contained six major phenolic compounds (quercetin -3-O- rutinoside, quercetin hexoside, quercetin rhamnosylhexoside hexoside, kaempferol rhamnosylhexoside, cyanidin -3-O- glucoside and cyanidin -3-O- rutinoside). After in vitro digestion, the contents of two anthocyanins were both decreased significantly, while the contents of four flavonoid glycosides were all increased. In addition, MBD was found to successfully suppress acrylamide-induced ROS overproduction, restore the mitochondrial membrane potential, and inhibit the mitochondrial membrane lipid peroxidation and glutathione depletion. More interestingly, the protective effect of MBD against acrylamide-induced oxidative damage was enhanced compared with mulberry fruits without digestion (MBE). Further study revealed that MBD enhanced the cell resistance capacity to acrylamide-induced oxidative stress, rather than its direct reaction with acrylamide. Overall, our results indicate that MBD provides a potent protection against acrylamide-induced oxidative stress.